Exploring the concept of extraordinary related to food tourists' nature-based experience. Issue 1 (2nd January 2017) - Goolaup, Sandhiya; Mossberg, Lena
ABSTRACT: The present study was undertaken in the context of a rise in the number of tourists travelling exclusively for food experiences. With the purpose of understanding what makes an extraordinary nature-based experience, non-participant observations and a number of interviews were carried out with food tourists visiting an oyster bar. The use of grounded theory as a data-analytic approach reveals a number of elements important in creating an extraordinary nature-based experience for the food tourists: non-ordinary, togetherness, insightful, hospitality, luxurious, genuine and peripheral.